Present indications and techniques of percutaneous nephrolithotomy: What the future holds? - Itay M. Sabler; Ioannis Katafigiotis; Ofer N. Gofrit; Mordechai Duvdevani (Asian Journal of Urology)
The purpose of the review was to present the latest updates on percutaneous nephrolithotomy (PCNL) procedure in terms of indications and evolving techniques, and to identify the advantages and disadvantages of each modality. The data for this review were collected after a thorough PubMed search in core clinical journals in English language. The key words included “PCNL” and “PNL” in combination with “indications”, “techniques”, “review” and “miniaturized PCNL”. Publications relevant to the subject were retrieved and critically reviewed. Current European and American Urology Association Nephrolithiasis Guidelines were included as well. The indications for standard PCNL have been changed through the past decade. Despite evolution of the procedure, innovations and the development of new technical approaches, the indications for miniaturized PCNL have not been standardized yet. There is a need for well-constructed randomized trials to explore the indications, complications and results for each evolving approach. A continuous reduction of tract size is not the only revolution of the last years. There is constant ongoing interest in developing new efficient miniature instruments, intracorporeal lithotripters and sophisticated tract creation methods. We can summarize that, PCNL represents a valuable well-known tool in the field of endourology. We should be open minded to future changes in surgical approaches and technological improvements. Keywords: Percutaneous nephrolithotomy, Nephrolithiasis, Intracorporeal lithotripsy, Lasers, Tract creation, Renal access, Horseshoe kidney, Calyceal diverticulum, Lower pole stones